2021
DOI: 10.1177/0271678x211010388
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular changes associated with epilepsy: A narrative review

Abstract: The blood-brain barrier (BBB) is dysfunctional in temporal lobe epilepsy (TLE). In this regard, microvascular changes are likely present. The aim of this review is to provide an overview of the current knowledge on microvascular changes in epilepsy, and includes clinical and preclinical evidence of seizure induced angiogenesis, barriergenesis and microcirculatory alterations. Anatomical studies show increased microvascular density in the hippocampus, amygdala, and neocortex accompanied by BBB leakage in variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 106 publications
1
34
0
Order By: Relevance
“…Altered vascular topology has been reported both acutely and long-term in adult models of status epilepticus. 22 To our knowledge there are no hyperacute (hours post SE) studies examining the vascular morphology nor studies examining the vascular consequences of FSE. Thus, Ndode-Ekane in a pilocarpine model of status epilepticus (SE) found reduced hippocampal vessel density, vessel length accompanied by increased blood-brain barrier (BBB) leak at 2 days post SE using immunohistochemical staining.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Altered vascular topology has been reported both acutely and long-term in adult models of status epilepticus. 22 To our knowledge there are no hyperacute (hours post SE) studies examining the vascular morphology nor studies examining the vascular consequences of FSE. Thus, Ndode-Ekane in a pilocarpine model of status epilepticus (SE) found reduced hippocampal vessel density, vessel length accompanied by increased blood-brain barrier (BBB) leak at 2 days post SE using immunohistochemical staining.…”
Section: Discussionmentioning
confidence: 99%
“…Increased vascular densities were found in the cortex and amygdala, days and weeks after adult rat pilocarpine and kainate-induced SE. 29,45 Within the hippocampus the overwhelming evidence is for increased microvascular density days to weeks after induced adult SE (see Table 1 in Marcon 22 for a concise summary). In our study we found increased vessel length in the hippocampus of FSE pups at 2 hrs after the cessation of SE that was mirrored by our fractal analyses (Figure 5(c)).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the missense variants associated with epilepsy were located in WD40 repeat domain or bromodomain. These evidences suggest that WD40 repeat domains and bromodomains of BRWD3 may play a crucial role in the pathophysiology of epileptogenesis by affecting cell signal transduction, epigenetic signaling reading, level of neurotransmitters, and neurovascular changes 33,34 . Further studies on the pathological consequences/neurological dysfunction are required to elucidate the essential link between the BRWD3 variants and epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, evaluating the relationship between cerebral microvasculature and epilepsy may lead to the development of new therapeutic targets. 8 …”
Section: Discussionmentioning
confidence: 99%